IMPLEMENTATION OF BUREAUCRACY REFORM THROUGH THE DEVELOPMENT AND IMPLEMENTATION OF SMART CITY IN CIMAHI CITY - Titin Rohayatin; Zaenal Abidin AS; Harky Ristala (Jurnal Academia Praja, 2023)
The reform of the government bureaucracy marks a change in the government structure to a decentralized pattern. Consequently, the implementation of regional autonomy has changed the entire structure and function of the bureaucracy and the implementation of public services. Bureaucratic reform and public services are two important elements in governance management in the era of globalization. Bureaucratic reform is the government's commitment to implementing good governance to be able to have high competitiveness through the application of the concept of e-Government, one of which is the implementation and development of Smart Cities. Smart City is a city that combines information and communication technology (ICT) with the aim of improving the performance of government services. Smart cities in the era of globalization and digitalization can have a big impact on changing the lives of individuals and government organizations. Information technology in the era of globalization is the main means of improving human resources as implementers of government organizational systems. The implementation and development of Smart City aims to develop smart solutions for dealing with the challenges of urbanization, globalization, and the use of sophisticated information technology based on e-government.